SPECIFIC FEATURES OF VILLAGE READING ROOM'S IN STAVROPOL REGION IN 1920-1930s - E. T. Golovina (Гуманитарные и юридические исследования)
The article studies specific features of village reading rooms in the context of Bolsheviks cultural policy. The new government took the concept up from the Russian Empire. Village reading rooms were supposed to provide cultural and educational activities in rural areas. Hard routine work, challenging financial state and illiteracy were the factors that impeded the process. Therefore, the staff of reading rooms carried out reference work. The funding partly rested with the people. Stavropol experience demonstrates both positive examples of village reading rooms activities, as well as examples of a formal approach.